2021
DOI: 10.1111/1440-1681.13461
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin attenuated the symptoms of mice model of systemic lupus erythematosus by restoring the Treg/Th17 balance

Abstract: The Treg/Th17 imbalance is associated with the development of systemic lupus erythematosus (SLE). Dihydroartemisinin (DHA), a semi‐synthetic derivative of artemisinin, is isolated from the traditional Chinese herb Artemisia annua Artemisia annua L. This study aims to evaluate the effects of DHA alone or in combination with prednisone in immunodeficiency of SLE. In vivo, the therapeutical effect of DHA alone or in combination with prednisone was assessed in the pristane‐induced SLE mouse model. Then, the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Li et al showed that senescence of myeloid-derived suppressor cells (MDSCs) promoted the pathogenesis of SLE, while dihydroartemisinin alleviated the manifestation of SLE by attenuating MDSC senescence via regulating Nrf2/HO-1 pathway ( 54 ). Subsequently, it was demonstrated that dihydroartemisinin alone, or in combination with prednisone treatment, significantly ameliorated the signs and symptoms of murine SLE through restoring the Treg/Th17 balance by reducing transcription of RORγt and increasing expression of Foxp3 in T cells ( 55 ). Serum levels of Macrophage migration inhibitory factor (MIF) in SLE patients were positively associated with the disease activity.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Li et al showed that senescence of myeloid-derived suppressor cells (MDSCs) promoted the pathogenesis of SLE, while dihydroartemisinin alleviated the manifestation of SLE by attenuating MDSC senescence via regulating Nrf2/HO-1 pathway ( 54 ). Subsequently, it was demonstrated that dihydroartemisinin alone, or in combination with prednisone treatment, significantly ameliorated the signs and symptoms of murine SLE through restoring the Treg/Th17 balance by reducing transcription of RORγt and increasing expression of Foxp3 in T cells ( 55 ). Serum levels of Macrophage migration inhibitory factor (MIF) in SLE patients were positively associated with the disease activity.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…The Th17/Treg cell imbalance not only plays a key role in RA but also plays an important role in systemic lupus erythematosus (SLE) and uveitis. The changes in cytokines secreted by Th17 and Treg cells are closely correlated with the pathogenesis of SLE and uveitis [ 22 , 23 ]. Therefore, we isolated spleen lymphocytes from different groups of RA rats and analyzed the Th17/Treg cell ratio by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of artemisinin mainly focus on the regulation of allergy, anti-allergy, immune regulation and fever suppression and detoxification (Çapcı et al, 2021). Recent studies have shown that artemisinin has a certain effect on systemic lupus erythematosus (Chen et al, 2021;Lin et al, 2021). Artemisinin exhibited anti-inflammatory activity and lowered the systemic levels of inflammatory cytokines that resulted in cytokine storm and inflammatory organ injury in high-risk COVID-19 patients (Uckun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%